2008
DOI: 10.1177/0731684407087755
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Laminations on Mechanical and Physical Properties of Hybrid Composites

Abstract: The mechanical properties of the vinyl ester reinforced with oil palm of empty fruit bunch fibers (EFB) laminated at different layer arrangements with glass fiber (CSM) composites were investigated. The EFB and CSM fibers were laminated at different layer arrangements and then were impregnated with vinyl ester resin using resin transfer molding (RTM). Post-cure was carried out after cool press for about 24 h in an oven at 508C. Six different layers of lamination with a ratio of 50/50 fiber composite (50% EFB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Most research on natural and synthetic fibre hybrid composites used glass fibres with natural fibres to reinforce a matrix. Because glass fibres have better mechanical properties than natural fibres, in general, it was shown that the tensile, 3056 flexural, 32,3436,3943,4547,4952,54,5760 compressive 57,61 properties, thermal stability 30,31,62 and water resistance 34,35,39,40,42,4952,54 were improved due to the introduction of glass fibres. Various results on the impact strength including both improved 34,35,…”
Section: Properties Of Hybrid Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research on natural and synthetic fibre hybrid composites used glass fibres with natural fibres to reinforce a matrix. Because glass fibres have better mechanical properties than natural fibres, in general, it was shown that the tensile, 3056 flexural, 32,3436,3943,4547,4952,54,5760 compressive 57,61 properties, thermal stability 30,31,62 and water resistance 34,35,39,40,42,4952,54 were improved due to the introduction of glass fibres. Various results on the impact strength including both improved 34,35,…”
Section: Properties Of Hybrid Compositesmentioning
confidence: 99%
“…The tensile and flexural strengths are shown in Figure 8, from which it is seen the hybrid composites exhibit improved properties compared to the EFB/polyester composites. Abdul Khalil et al 50 investigated the mechanical properties of vinyl ester composites reinforced with oil palm of empty fruit bunch fibres (EFB) and glass fibres (CSM) laminated at different layer arrangements. The mechanical properties and water resistance showed improvement.…”
Section: Properties Of Hybrid Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat a waste of resources as there are numerous reports on plant biomass fibers being utilized for their excellent and outstanding properties. Among the usages include the reconditioning and converting the biomass into nanoparticles into reinforcing fillers in enzyme support and as renewable sources for making pulp and paper [5,9,10]. Plant fibers have been successfully re-fashioned into bio-composite and hybrid composites for the furniture industry, too [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, there has been tremendous interest in the use of natural fibers for the manufacturing of polymer composites . The hybrid composites based on polymer matrix and natural fibers such as wood flour and cellulose flour are valued materials with a great mechanical and thermal properties as well as enormous prospective applications in many areas of life …”
Section: Introductionmentioning
confidence: 99%